Understanding Muhammadiyah's Role in Non-Formal Institutions as an Islamic Movement in Facing the Covid -19 - Ilda Cita Suci; Napsuparmna Napsuparman; Rusma Rusman; Elihami Elihami (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
Muhammadiyah is an Islamic movement, a daqwah amar ma'ruf nahi munkar movement and even a tajdid movement. Therefore, those who deserve to win Muhammadiyah are the ones who really determine the goals of K. Ahmad Dahlan to establish Muhammadiyah.Association in Muhammadiyah is charity and plays a total role with Islam and for Islam itself. Islam is a rule that covers all fields such as creed, worship, morals, justice, culture, art, science, love, law, power, work, wealth, politics, social, economy, as well as da'wah, jihad and thought. Understand that Al- The Quran is a reference for every Muslim to know Islamic law. Given the role of muhammdiyah as an Islamic movement that is so important and is associated with the emergence of the COVID-19 virus which has caused unrest in many countries around the world. COVID-19 is an infectious disease caused by a newly discovered type of coronavirus. This new virus and the disease it caused was unknown before the outbreak in Wuhan, China, in December 2019. COVID-19 is now a pandemic that has occurred in many countries around the world. Including in Indonesia the spread is very fast.